Spatial distribution of crystalline corrosion products formed during corrosion of stainless steel in concrete. (May 2015) - Serdar, Marijana; Meral, Cagla; Kunz, Martin; Bjegovic, Dubravka; Wenk, Hans-Rudolf; Monteiro, Paulo J.M.
Abstract: The mineralogy and spatial distribution of nano-crystalline corrosion products that form in the steel/concrete interface were characterized using synchrotron X-ray micro-diffraction (μ-XRD). Two types of low-nickel high-chromium reinforcing steels embedded into mortar and exposed to NaCl solution were investigated. Corrosion in the samples was confirmed by electrochemical impedance spectroscopy (EIS). μ-XRD revealed that goethite ( α -FeOOH) and akaganeite ( β -FeOOH) are the main iron oxide–hydroxides formed during the chloride-induced corrosion of stainless steel in concrete. Goethite is formed closer to the surface of the steel due to the presence of chromium in the steel, while akaganeite is formed further away from the surface due to the presence of chloride ions. Detailed microstructural analysis is shown and discussed on one sample of each type of steel. Highlights: Synchrotron micro-diffraction used to map the distribution of crystalline phases. Goethite and akaganeite are the main corrosion products during chloride induced corrosion in mortar. Layers of goethite and akaganeite are negatively correlated. EDS showed Cr present in corrosion products identified by SEM.